Emotion Regulation and Mindful Parenting in Early Childhood: The Role of Moderating Social Support - Ferdian Utama; Ika Ariyati; Yuliatur Rohimah; Yeasy Agustina Sari (CV. Creative Tugu Pena, 2025)
This study aimed to examine the effect of emotion regulation on mindful parenting among parents of young children and to investigate the moderating role of social support in this relationship. A quantitative approach with a non-experimental causal-associative design was employed. The sample consisted of 202 parents of children aged 3–6 years who were enrolled in Raudhatul Athfal (RA) schools in Metro City, Lampung, Indonesia. Data were collected using a questionnaire comprising the Emotion Regulation Questionnaire (ERQ) to assess emotion regulation, the Interpersonal Mindfulness in Parenting Scale (IM-P) to measure mindful parenting, and the Multidimensional Scale of Perceived Social Support (MSPSS) to evaluate social support. Data were analyzed using Moderated Regression Analysis (MRA). The findings revealed that emotion regulation had a positive and significant effect on mindful parenting (β = 0.56, p < .001). Social support also showed a positive and significant effect on mindful parenting (β = 0.41, p < .001). Furthermore, the moderation analysis indicated that social support significantly strengthened the relationship between emotion regulation and mindful parenting (p = .009). These findings suggest that mindful parenting is influenced by both internal parental factors, such as emotion regulation, and external contextual factors, such as social support. Therefore, enhancing parents’ emotion regulation skills and strengthening social support from family and community environments are important strategies for promoting more mindful and responsive parenting practices during early childhood.